Summer work and injury among middle school students, aged 10–14 years. Issue 6 (18th May 2004) - Zierold, K M; Garman, S; Anderson, H
Abstract : Background: Little information exists on injury and factors associated with injury in working youth aged 10–14 years. Most studies do not involve children younger than 15. Methods: A cross-sectional anonymous survey was administered to middle school students in five school districts and one large urban school in October 2001. Results: Of the 3189 working middle school students who responded to the survey, the majority were employed in informal job settings, such as working for someone in a home, newspaper delivery, and working on family farms or in family businesses. Overall, 18% of children reported being injured at work. Of those injured, 26% reported that their injury was severe enough to affect their activities for more than three days. Variables that were associated with injury included having a "near-miss" incident at work (AOR 6.61, 95% CI 4.92 to 8.89), having a co-worker injured (AOR 2.65, 95% CI 1.95 to 3.60), and being asked to do something dangerous (AOR 2.25, 95% CI 1.61 to 3.14). Conclusions: Children are working and being injured in jobs that are not covered by existing child labour laws. Injury rates in non-covered occupations are high, warranting review of current laws.